2011
DOI: 10.5539/ass.v7n5p98
|View full text |Cite
|
Sign up to set email alerts
|

In the Context of Visual Pollution: Effects to Trabzon City Center Silhoutte

Abstract: One of the clearest indicators of visual pollution in the cities are their silhouettes. Silhouettes are the faces of physical structure and historical accumulation of cities. But today many cities are full of buildings that are incompatible with each other, that are disrespectful to the environment and that have no identity. Generally, city silhouettes consist of concrete façades, they have changed into common appearances that do not stamp themselves in people's minds, and the historical environments have disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 2 publications
0
19
0
6
Order By: Relevance
“…For the purpose of this study, Visual Pollution Sensitivity Scale was created. Based on literature analysis (Yilmaz & Sagsoz, 2011) the elements considered to be responsible for the visual chaos was isolated. The final scale consisted of 11 items (Cronbach's Alpha = 0.90): power distribution unit, multicolored building facades, PCV banners, billboards, satellite dishes, bus/tram stops covered with advertisements, electric cables, gas stations, garages, advertisement placed on storefronts, wheelie bin stores.…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of this study, Visual Pollution Sensitivity Scale was created. Based on literature analysis (Yilmaz & Sagsoz, 2011) the elements considered to be responsible for the visual chaos was isolated. The final scale consisted of 11 items (Cronbach's Alpha = 0.90): power distribution unit, multicolored building facades, PCV banners, billboards, satellite dishes, bus/tram stops covered with advertisements, electric cables, gas stations, garages, advertisement placed on storefronts, wheelie bin stores.…”
Section: Methodsmentioning
confidence: 99%
“…The degree to which the visual cortex of the brain is stressed is directly related to the light frequency and variety to which it is exposed (Gokhale et al, 2011). Some studies demonstrated that visual pollution may lead to distraction, decrease in opinion diversity, and loss of identity, traffic congestion, health hazards of diverse kinds, irritability and psychological disturbances, eye fatigue, loss of sense of hygiene, and aesthetics (Gokhale et al, 2011;Yilmaz, 2011). In addition, children closely associated with visual pollution from childhood are generally forbidden of subtle aesthetics and they get used to this unsightly surroundings, even lose their natural desire to change it (Milan & De, 2015).…”
Section: Hijazi Rola (Phd)mentioning
confidence: 99%
“…In other sources of information visual pollution is determined as the phenomenon that causes damage in the sense of beauty and the breakdown of aesthetic considerations and satisfaction and acceptance of the image of the ugly (Mohamed et al, 2011); that makes some negative changes in the natural environment and, in this way, turns the visual areas into something that disturbs people (Yilmaz et al, 2011;Nagle, 2009). Magnitude of visual pollution depends on the number of affected persons, on the distance between them and the observed object, and also depends on the orography of the terrain between the observation point and the observed object (Garcia-Garrido et al).…”
Section: International Experiencementioning
confidence: 99%